A Critical Discourse Analysis of Online Media on the Indonesian Government’s Handling of BPJS Kesehatan Fraud - I Gusti Agung Ayu Rahma Praminia; Adelia Dias Triyanti; Ni Putu Diah Eta Tritintya; Ruth Vidyadanu Sekarpratiwi; I Komang Triska Ananda Dilivianugraha Priantara (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2026)
The National Health Insurance (JKN) program has been reported by the media in relation to fraud cases, which are framed not only as legal violations but also as issues of public service governance. This study aims to examine how online news media construct narratives, meanings, and power relations surrounding the JKN fraud issue. Employing a qualitative approach and Van Dijk’s Critical Discourse Analysis framework, which includes the dimensions of text, social cognition, and social context, this study analyzes three news articles published by Kompas.com, Detik.com, and Kumparan.com. The findings reveal that each media outlet constructs the discourse on JKN fraud through distinct emphases. Kompas frames fraud as a systemic problem involving networks of power, Detik highlights administrative responses and state-imposed sanctions with limited transparency, while Kumparan emphasizes cross-institutional collaboration as the proposed solution. Overall, media discourse tends to position the state as a dominant and solution-oriented actor, while critical discussion of the JKN policy structure and oversight mechanisms remains limited. These findings indicate that the media play a crucial role in shaping public understanding of JKN fraud and in representing power relations among the government, hospitals, and regulatory institutions within health policy discourse.